Development as a form of religious engineering? Religion and secularity in development discourse - Haustein, Jörg 1975- (2021)
The burgeoning literature on religion and development tends to frame development as a project of post-WWII secular modernism and hence postulates a new ‘discovery of religions’ in development discourse. This perception is based on a two-fold forgetfulness of history. On the one hand, the colonial genealogy of development in the ‘civilising mission’ came with a decisive Christian input. On the other hand, the notion of secular modernism conceals the conceptual interconnectedness of religion and secularity in Western debates from the neoclassical secularization theories to the recent ‘return of God’ narratives. Drawing out the contours of a long history of international development, the article argues that scholarship needs to move beyond simple diagnoses of the presence or absence of religion in development discourse, but highlight how the ideology of development has tended to follow narratives about progress and values that are closely connected to discourses about global religion and secularity.
Keywords: Modernity; Christian Missions; faith-based organization; Return of Religion; Secularization; Colonialism; Religion; Development